2018
DOI: 10.3847/1538-4357/aada10
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Coronal Mass Ejection Properties on Their Solar Source Active Region Characteristics and Associated Flare Reconnection Flux

Abstract: The near-Sun kinematics of coronal mass ejections (CMEs) determine the severity and arrival time of associated geomagnetic storms. We investigate the relationship between the deprojected speed and kinetic energy of CMEs and magnetic measures of their solar sources, reconnection flux of associated eruptive events and intrinsic flux rope characteristics. Our data covers the period 2010-2014 in solar cycle 24. Using vector magnetograms of source active regions we estimate the size and nonpotentiality. We compute … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 91 publications
2
25
0
Order By: Relevance
“…Because of the pressure imbalance between the CME and the surrounding solar wind upon insertion in the heliospheric domain (leading to an expansion of the CME structure, as shown by Scolini et al 2019Scolini et al , 2021, the effective initial CME speed is ∼ 1100 km s −1 , which results in a fast CME that drives an interplanetary shock and sheath, as discussed in Section 3. Such a combination of initial parameters is representative of those of a typical fast CME with a reconnected flux of the order of 10 14 Wb (Pal et al 2018). The CME initial direction is chosen to reproduce two end-member scenarios of interaction with different solar wind structures (shown in panels (b) and (d) in Figure 1): in run A, the CME is inserted across the HCS/HPS at (θ, φ) = (0 • , 0 • ); in run B, the CME is inserted across the HSS at (θ, φ) = (5 • , 0 • ), in a configuration similar to that of CMEs originated from "anemone" active regions (e.g.…”
Section: Modeling Set-upmentioning
confidence: 99%
“…Because of the pressure imbalance between the CME and the surrounding solar wind upon insertion in the heliospheric domain (leading to an expansion of the CME structure, as shown by Scolini et al 2019Scolini et al , 2021, the effective initial CME speed is ∼ 1100 km s −1 , which results in a fast CME that drives an interplanetary shock and sheath, as discussed in Section 3. Such a combination of initial parameters is representative of those of a typical fast CME with a reconnected flux of the order of 10 14 Wb (Pal et al 2018). The CME initial direction is chosen to reproduce two end-member scenarios of interaction with different solar wind structures (shown in panels (b) and (d) in Figure 1): in run A, the CME is inserted across the HCS/HPS at (θ, φ) = (0 • , 0 • ); in run B, the CME is inserted across the HSS at (θ, φ) = (5 • , 0 • ), in a configuration similar to that of CMEs originated from "anemone" active regions (e.g.…”
Section: Modeling Set-upmentioning
confidence: 99%
“…Because of the difficulty in observing CME evolution and measuring CME acceleration in the low corona, many studies instead compare the CME velocity measured at a few solar radii after the peak acceleration phase, and the total magnetic flux reconnected during the flare. These studies found that, in fast CME events, these two quantities are positively correlated (Qiu & Yurchyshyn 2005;Deng & Welsch 2017;Toriumi et al 2017;Tschernitz et al 2018;Pal et al 2018). Note that most of these studies have focused on fast CMEs and strong flares, and it is unclear whether this relationship applies to a broader range of CMEs, in particular, slow CMEs.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus not possible to extract information for the magnetic flux of the CME using cotemporal magnetogram-based approaches (e.g. see Dissauer et al 2018a,b;Pal et al 2018;Dissauer et al 2019;Sarkar et al 2020). In this case, a base value of 80.0 × 10 12 Wb was used for the EUHFORIA runs, which represents the toroidal flux and is related to the magnetic field strength via equation 7 given in Verbeke et al (2019b).…”
Section: Magnetic Flux and Helicity Signmentioning
confidence: 99%